Bis(pyrazolyl)methanetetracarbonyl-molybdenum(0) as precursor to a molybdenum(VI) catalyst for olefin epoxidation - Figueiredo, Sonia
Bis(pyrazolyl) methanetetracarbonyl-molybdenum(0), cis-[Mo(CO)(4)(BPM)] (1), was prepared from Mo(CO)(6) and the ligand bis(pyrazolyl) methane (BPM), and examined as a catalyst precursor for the epoxidation of olefins using tert-butylhydroperoxide (TBHP) as oxidant. Catalytic activities followed the sequence 1-octene < trans-2-octene < alpha-pinene < (R)-(+)-limonene < cis-cyclooctene, and, with the exception of alpha-pinene and limonene, the corresponding epoxide was always the only reaction product. Turnover frequencies for the epoxidation of cyclooctene were 580 mol mol(Mo)(-1) h(-1) at 55 degrees C and 1175 mol mol(Mo)(-1) h(-1) at 75 degrees C, which compare favourably with those found for other molybdenum carbonyl complexes used as catalyst precursors for the same reaction under similar conditions. Catalytic activities were lower in the presence of organic co-solvents, decreasing in the sequence 1,2-dichloroethane > nitromethane > ethanol > hexane > acetonitrile. It is proposed that the oxodiperoxo complex [MoO(O-2)(2)(BPM)] (2) may be the active catalyst formed in situ by oxidative decarbonylation of 1, since crystals of 2 suitable for structure determination by X-ray diffraction were obtained from the reaction solution recovered after a catalytic run at 55 degrees C with cis-cyclooctene as substrate. In support of this hypothesis, the catalytic performance of 2 for the epoxidation of cyclooctene at 55 degrees C is very similar to that for 1. (C) 2012 Elsevier B. V. All rights reserved.